Liver Fibrosis and Hepatitis B Coinfection among ART Naïve HIV-Infected Patients at a Tertiary Level Hospital in Northwestern Tanzania: A Cross-Sectional Study - Semvua B. Kilonzo; Daniel W. Gunda; Flora Kashasha; Bonaventura C. Mpondo (Journal of Tropical Medicine)
Background. Liver fibrosis which is a common complication of chronic hepatitis B infection is rarely diagnosed in low-resource countries due to limited capacity to perform biopsy studies. Data on the utilization of noninvasive techniques which are feasible for diagnosis of liver fibrosis in these settings among HIV-infected patients is scarce. The objective of this study was to establish the magnitude of liver fibrosis by using both aspartate-aminotransferase-to-platelets ratio and fibrosis-4 scores with associated hepatitis B coinfection among antiretroviral therapy naïve HIV-infected patients. Methods. We reviewed data of 743 adult patients attending HIV clinic with available hepatitis B surface antigen test results. Baseline clinical information was recorded and aspartate-aminotransferase-to-platelet ratio and fibrosis-4 scores were calculated. The cut-off values of 1.5 and 3.25 were used for diagnosis of significant fibrosis by aspartate-aminotransferase-to-platelets ratio and fibrosis-4 scores, respectively. Results. The prevalence of liver fibrosis was 3.5% when aspartate-aminotransferase-to-platelet score was used and 4.6% with fibrosis-4 score and they were both significantly higher among patients with hepatitis B coinfection. Younger patients with HIV advanced disease and elevated liver transaminases had increased risk of having hepatitis B coinfection. Conclusion. A remarkable number of HIV-infected patients present with liver fibrosis, predominantly those with hepatitis B infection.